Test av modeller för prioritering av förändringsförslag i Stora Enso Skog AB´s nya produktionsplaneringssystem VSOP - Ohls, Anders (2010)
In order to evaluate the benefits and costs associated to investments in information technology (IT) managers need to be aware of the complexity in the nature of the task. Hence all the benefits that arise from the investment are not of pure economic character. The complexity of the task is even more obvious when managers also need to prioritize between a number of possible investments in order to fit a given budget. Stora Enso Skog AB is about to implement a new administration system to the organisation and due to that they will also implement a new standard system for the production planning process. In order to seek the modifications in the standard system that needs to be done to fit the organisations way of working, the managers have put together a reference group to seek out these modifications. The aim with this report is to identify a model that can prioritize these suggested modifications and test it practically with a group of future system users. The first part of the report is a literature study to map the existing models that are available. These models were put up to a test of acceptance to see which models that stand up to the criteria that the managers formulated initially. This test resulted in the choose of a model called 5-modellen. In order to examine the chosen model, a group of future system users were set to test the model in practice. The results from the practical test of 5-modellen showed that the model matched almost all the expectations that the mangers had on the model they chose. In the case the model did not meet the expectations, the failure is not to be interpreted as if the wrong model was chosen. In order to give some practical advice to future evaluations using 5-modellen, the study shows that the participants in the practical evaluation of an IT investment need more time for preparation and they have to be well known with the system that is put up to evaluation.